2021
DOI: 10.1002/admi.202100704
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Voltage‐Dependent Oxidation Mechanisms of Poly(Ethylene Oxide)‐Based Solid Electrolytes for Solid‐State Batteries

Abstract: Using galvanostatic techniques, an oxidative stability up to 4.6 V versus Li/Li+ and beyond has been reported for the prototypical polymer electrolyte consisting of 1 m lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in poly(ethylene oxide) (PEO). However, no long‐term cycling of a battery with this high cut‐off voltage has been demonstrated. Electrochemical and spectroscopic/spectrometric methods are employed to critically reinvestigate the electrochemical oxidation mechanisms of PEO electrolytes. It is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 42 publications
9
41
0
14
Order By: Relevance
“…[95,106] Nonetheless, a recent study reported an increase in the oxidative stability from 4.05 to 4.3 V versus Li/Li + , for PEG and PEGDME-based electrolytes, respectively. [107] Accordingly, a higher reactivity of the terminal hydroxyls would be in agreement with the early oxidation of hydroxyls in PEO reported by Seidl et al [105] Another recent study reported higher oxidative stability for a cross-linked polymer electrolyte containing free hydroxyls compared to PEG, which was caused by the restricted mobility and reactivity of the hydroxyls in the cross-linked electrolyte. [108] The diverging results reported in the recent literature or their conflicting interpretation indicate that the evaluation of the absolute stability limit of PEO-based electrolytes is still challenging.…”
Section: Intrinsic Oxidative Stability Of Polyether Electrolytessupporting
confidence: 85%
See 4 more Smart Citations
“…[95,106] Nonetheless, a recent study reported an increase in the oxidative stability from 4.05 to 4.3 V versus Li/Li + , for PEG and PEGDME-based electrolytes, respectively. [107] Accordingly, a higher reactivity of the terminal hydroxyls would be in agreement with the early oxidation of hydroxyls in PEO reported by Seidl et al [105] Another recent study reported higher oxidative stability for a cross-linked polymer electrolyte containing free hydroxyls compared to PEG, which was caused by the restricted mobility and reactivity of the hydroxyls in the cross-linked electrolyte. [108] The diverging results reported in the recent literature or their conflicting interpretation indicate that the evaluation of the absolute stability limit of PEO-based electrolytes is still challenging.…”
Section: Intrinsic Oxidative Stability Of Polyether Electrolytessupporting
confidence: 85%
“…[ 107 ] Accordingly, a higher reactivity of the terminal hydroxyls would be in agreement with the early oxidation of hydroxyls in PEO reported by Seidl et al. [ 105 ] Another recent study reported higher oxidative stability for a cross‐linked polymer electrolyte containing free hydroxyls compared to PEG, which was caused by the restricted mobility and reactivity of the hydroxyls in the cross‐linked electrolyte. [ 108 ]…”
Section: Chemical and Electrochemical Stability Of Hvlp Cellssupporting
confidence: 77%
See 3 more Smart Citations